Eksistensi Tembang Mamaca (Macapat) dalam Dimensi Kultur, Mistik dan Religius: Studi Etnografi Tembang Mamaca di Desa Serabi Barat Modung Bangkalan - Fathul Khoiriyah; Zainuddin Syarif (Tribakti: Jurnal Pemikiran Keislaman, 2019)
This study examines the historical terminology of mamaca (macapat) in the Modung Bangkalan West Serabi Village. "The focus of the study is" How is the existence of the Macapat songs in the cultural, the mystical and religious dimensions of the Modung Bangkalan West Serabi Village community? " The West Serabi Village community, the mystical and religious dimensions of Modung Bangkalan. The results of the study concluded and explained that the elements of the West's Song (macapat) in the Modung Bangkalan consist of: (1) personal beliefs about the old teachings as a truth, (2) the public's heritage in always upholding ancestral heritage, (3) the teachings of goodness in the world that are relevant to the culture of society, (4) customs that tend to be mystically influenced by old cultures that are still used from generation to generation, ( 5) The value and guidance of many and individual citizens.